Evaluation on Implementation of Performance Management in Asuransi Jiwa Bersama (AJB) Bumiputra 1912 - Sri Nurcahyati (Journal of Business and Behavioural Entrepreneurship, 2017)
This study aimed to evaluate the implementation of performance management in AJB Bumiputera 1912. This study uses DEM (Discrepancy Evaluation Method) evaluation method. The components that were evaluated are the component of design, installation, implementation, and outcome. The methods used in this study is a questionnaire on 51 unit leader respondents at the headquarter and regional offices, the 150 employees of the central office, the interview method on 10 respondents, observation and study documentsmethod. The results of this study indicate that there is a gap between the actual conditions (Performance) with the condition that should be happened (Standard) on all four components that were analyzed. In conclusion, it is necessary to do some improvements to reduce the gap so that the actual conditions more closely the conditions that should be happened. The improvements that need to be done are alignment of the performance management design with the needs of company at this time, the need for commitment to change from the top down, implementation of reward and punishment continuously,and the need to support tools and technologies that were integrated, so the individual and team performance increased and imply to organization performance to be a leading position in life insurance industries in Indonesia.